PENERAPAN STRATEGI AUTONOMY LEARNING PADA PEMBELAJARAN BAHASA INGGRIS DALAM LINGKUNGAN DARING/BAURAN - Rina Husnaini Febriyanti; Hanna Sundari (Universitas PGRI Sumatera Barat, 2022)
The Community Service was held in SMK Amaliyah that located in Srengseng Sawah Jagakarsa, Jakarta Selatan purposed to conduct teacher training in terms of implementation of autonomy learning (AL) strategy for the student particularly in English language instruction in the online/blended environment. The training was organized both theoretically and practically related to the AL topic. Additionally, the detailed deployment of how to practice in the classroom was applied. The Community service activities were implemented in the form of training for teachers who teach at SMK Amaliyah. The method used in the training of community service activities used Community Language Learning, which is a method in which each other shares information and discusses and shares experiences like consultants and clients. This Community Service activity is carried out in the odd semester of the 2021/2022 Academic Year. In addition, this article also presents the participants' perceptions that involve reaction, learning, behavior, and result.